2019
DOI: 10.4149/gpb_2019036
|View full text |Cite
|
Sign up to set email alerts
|

Impact of obesity and gender differences on electrodermal activities

Abstract: The widespread use of electrodermal activity (EDA) as a measuring tool in sympathetic nervous system activity researches has resulted in a wide variety of publications on EDA. Yet, the influences of obesity and gender differences in the responses and levels of EDA have not been studied carefully. This study aims to investigate the impacts of obesity and gender differences on EDA parameters. To this end, EDA responses and levels were recorded from 36 (18 males and18 females) apparently healthy adult subjects ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Further, excess body fat may contribute to differences in electrodermal activity. For example, a study that compared obese and non-obese cis -men and women found that skin conductance responses differed significantly depending on obesity status across sex ( Aldosky, 2019 ), possibly due to subcutaneous fat eliciting greater sweat production ( Shipman and Millington, 2011 ; Yosipovitch et al, 2007 ). However, more studies are needed to understand this association more fully.…”
Section: Limitations and Pitfalls Of Using Wearables In Researchmentioning
confidence: 99%
“…Further, excess body fat may contribute to differences in electrodermal activity. For example, a study that compared obese and non-obese cis -men and women found that skin conductance responses differed significantly depending on obesity status across sex ( Aldosky, 2019 ), possibly due to subcutaneous fat eliciting greater sweat production ( Shipman and Millington, 2011 ; Yosipovitch et al, 2007 ). However, more studies are needed to understand this association more fully.…”
Section: Limitations and Pitfalls Of Using Wearables In Researchmentioning
confidence: 99%
“…everyday stress responses in natural environment (Vavrinsky et al 2021). Thus, EDA measurement as a non-invasive and sensitive method is increasingly used in psychophysiological research (Posada-Quintero et al 2016;Aldosky 2019;Posada-Quintero and Chon 2020).…”
Section: Introductionmentioning
confidence: 99%